Allomorph Analysis In The Book Entitled “The Practice Of English Language Teaching” By Jeremy Harmer (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyse allomorph in the book The Practice of English Language Teaching by Jeremy Harmer, especially in chapter 3 “Background Issues in Language Learning”. The method used is descriptive qualitative with purposive sampling technique and document analysis. The data were analysed based on the pronunciation variations of the suffix -s or -es (plural), -ed (past tense), and irregular form (suppletion). This study found that the -s or -es allomorph is devided into three pronunciation categories : /s/, /z/, and /iz/, while the -ed allomorph consist of /t/, /d/, and /id/. Suppletion is found in partial (e.g., teach à taught, bring à brought ) and full (good à better à best) forms. The most dominant allomorph category is the suffix /d/ (29,11%), followed by /z/ (24,68%), and /s/ (12,3%). This study provides insights into patterns of word form variation and English that are relevant for language learning, helping teachers and learners understand the phonological and morphological aspects of language better.